Peran Islam dan Ilmu Pengetahuan dalam Menjawab Tantangan Global - Siraiya IT (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
Islam is a global and universal religion. His objection is to present a perfect and universal civilization spiritually, morally, or materially. Knowledge is one of the most important aspects of human life, which is hoped to educate the life of a nation. Nevertheless, the knowledge cannot be independent from religion. Knowledge has been integrated with religion as it has united with every sphere of human life. The advance of technology and globalization make the gap between knowledge and religion further. Therefore, courses of Islamic thought play an important role to synergize the both aspects. Because according to Islam, religion does not only confirm the knowledge but he is also become a source of information to advance knowledge. Even more, religion itself is paradigm for advancing the knowledge. Without religion, knowledge will miss new inspirations to progress. Equally, religion will be exclusive without knowledge.